Warunki i perspektywy rozwoju budżetów terenowych w Polsce - Wierzbicki, Janusz (Wydział Prawa i Administracji UAM, 1966)
We speak about the autonomy of national councils if and when they are entitled to undertake economic, social and cultural activities in a defined framework, have at their disposal a range of social, cultural and municipal facilites and are provided with indispensable financial and material means. The regional budgets do not draw any distinctions between the means allocated to the financing of tasks undertaken relatively autonomically by the regional authorities themselves and the means allocated for carrying out activites commissioned to the national councils by the central authorites. For that reason precisely the problem of financial autonomy of national councils is strictly related with these two spheres of their activities. The practice up to now restricted the said problem mainly to the revenue side of the regional budgets. The financial system of national councils comprises: the financial economy of regional and municipal enterprises (the paper does not dwell on that subject), the budget economy — consisting of the plannig and carrying out of the national councils' tasks, the problems of regional revenues and the non budgetary economy, in which the most important role is played by the management of the purpose- - defined funds of the national councils. To the competency of local authorities belong generally such tasks which are related with satisfying the normal social needs. The same kinds of facilites can, however, be subordinated partially to the central authorities and partially to the national councils of different levels. The endeavors to put one kind of facilities under the exlusive competency of either the central authorities or the national councils — would not be realistic. It does not also seem advisable to restrict the financial links of regional enterprises only to the budget of the national council to which they are subordinated as has been practised up to now. The competency of the national councils are defined by central authorities in following framework: 1)prices and fees, 2) principles regulating the division of income in the socialized enterprises and principles governing the tax policy in regards to the non-socialized economy and in regards to earned incomes, 3) the normatives of the social-cultural, educational, communal and dwelling facilities and 4) indices of financial means. The activity of the local authorities is limited at last but not least by the structure and size of the budgetary incomes of the national councils.